2011
DOI: 10.1038/cddis.2011.76
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol inhibits aminoglycoside-induced ototoxicity via heat shock protein 32

Abstract: Hearing loss is often caused by death of the mechanosensory hair cells of the inner ear. Hair cells are susceptible to death caused by aging, noise trauma, and ototoxic drugs, including the aminoglycoside antibiotics and the antineoplastic agent cisplatin. Ototoxic drugs result in permanent hearing loss for over 500 000 Americans annually. We showed previously that induction of heat shock proteins (HSPs) inhibits both aminoglycoside-and cisplatin-induced hair cell death in whole-organ cultures of utricles from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Heat shock protein (HSP) induction is a critical stress response in the inner ear that can promote survival of hair cells exposed to both classes of ototoxic drugs (1)(2)(3)(4)(5). Given that HSP induction is a ubiquitous response to stress (6), we hypothesized that sound that is loud enough to stress the inner ear without causing permanent damage would induce HSPs and inhibit ototoxic drug-induced hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock protein (HSP) induction is a critical stress response in the inner ear that can promote survival of hair cells exposed to both classes of ototoxic drugs (1)(2)(3)(4)(5). Given that HSP induction is a ubiquitous response to stress (6), we hypothesized that sound that is loud enough to stress the inner ear without causing permanent damage would induce HSPs and inhibit ototoxic drug-induced hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the anti-ototoxicity property of Celastrol has been revealed recently through induction of heat shock protein 32 to suppress both aminoglycoside- and cisplatin-induced hair cell death. 20 Moreover, Celastrol administration significantly rescued the hearing loss in mice receiving systematic aminoglycoside treatment. Mechanistically, Celastrol induced HSP32 expression, which in turn inhibited pro-apoptotic c-Jun N-terminal kinase (JNK) activation and hair cell death.…”
Section: Discussionmentioning
confidence: 97%
“…Mechanistically, Celastrol induced HSP32 expression, which in turn inhibited pro-apoptotic c-Jun N-terminal kinase (JNK) activation and hair cell death. 20 In view of the protective effect of Celastrol on aminoglycoside antibiotics and anti-neoplastic agent caused hair cell death, 20 here we sought to investigate the potential benefit of Celastrol on inner ear stem cells, which is believed to be permanently dormant in adult mammalian auditory system. In line with the protective effect against ototoxicity, here we demonstrated that 2 μM Celastrol treatment remarkably improved the viability and proliferation of isolated inner ear stem cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The triterpene compound celastrol has been shown to protect vestibular and cochlear hair cells from aminoglycoside toxicity (Francis et al 2011 ). Celastrol's protective activity appears to be through induction of Hsp32 expression, which occurs even in an Hsf1 null mutant background, and is associated with inhibition of JNK-mediated apoptosis.…”
Section: Protective Pathwaysmentioning
confidence: 99%